Chemotherapy Versus Chemotherapy Plus Chemoradiation as Neoadjuvant Therapy for Resectable Gastric Adenocarcinoma: A Multi-institutional Analysis. Issue 4 (October 2021) - Allen, Casey J.; Pointer, David T.; Blumenthaler, Alisa N.; Mehta, Rutika J.; Hoffe, Sarah E.; Minsky, Bruce D.; Smith, Grace L.; Blum, Mariela; Mansfield, Paul F.; Ikoma, Naruhiko; Das, Prajnan; Ajani, Jaffer; et al.
Abstract : Objective: We compare neoadjuvant chemotherapy (CT) to neoadjuvant chemotherapy plus chemoradiation (CRT) for patients with gastric adenocarcinoma (GA). Summary of Background Data: The optimal neoadjuvant therapy regimen for resectable GA is not defined. Methods: Utilizing data from 2 high-volume cancer centers, we analyzed patients who underwent surgery for localized GA from 1/1/2000-12/31/2017. Standard CT regimens were used according to treatment period. We compared propensity matched cohorts based on age, sex, race, histology, and clinical stage. Results: Four-hundred five patients (age 62 ± 12 year, 58% male, 56% White) were analyzed. 231 (57%) received CRT and 174 (43%) received CT. Groups differed based on histopathologic characteristics including preoperative stage ( p = 0.013). To control for these differences, propensity matched cohorts of 113 CT and 113 CRT patients were compared. CRT had similar frequencies of microscopically negative resections to CT (93% vs 91%, p = 0.81), but higher rates of complete pathologic response (15% vs 4%, p = 0.003) and lower pathologic stage ( p = 0.002). Completion of intended perioperative therapy occurred in 63% of CT and 91% of CRT patients ( p < 0.001). Median DFS was 45mo (95%CI: 20–70) in the CT group and 113mo (95%CI: 75–151) in the CRT group ( p = 0.018). Median OS was 53mo (95%CI: 30–77) versus 120mo (95%CI: 101–138); p = 0.015. Conclusions: In this multi-institutional comparison of neoadjuvant CT and CRT for resectable GA, CRT is associated with higher rates of completed perioperative therapy, higher rates of complete pathologic response, lower pathologic stage, and improved survival. Level of Evidence: Level III